ANALYSIS THE IMPACT OF SALES PROMOTION AND HEDONIC TO CONSUMER ONLINE IMPULSIVE BUYING ON SHOPEE USERS IN MANADO - Egalita Rosari Maria Sumampouw; Merinnda H.C. Pandowo (Universitas Sam Ratulangi, 2022)
The development of information and communication technology is very rapid. this is inseparable from the role of the internet in accessing information and communication. now the internet has become a community need, as internet users are increasing from year to year, this can be used as a potential market for ecommerce. One of the e-commerce that is in great demand by consumers is Shopee. The amount of competition in the e-commerce business requires business people to be able to understand consumer behavior in order to make purchases of the goods and services offered. Impulsive buying is an attractive consumer behavior for business people, with this impulsive action the products and services offered will be easier to sell. This study aims to determine: the impact of sales promotion on impulsive buying; hedonic impact on impulsive buying; and the impact of sales promotion and hedonic simultaneously on impulsive buying on Shopee e-commerce consumers. sampling technique using non-probability sampling. data obtained by distributing questionnaires to 120 respondents. The data analysis technique in this study was descriptive analysis using SPSS 25. The results showed that: sales promotion had no effect on impulsive buying; hedonic effect on impulsive buying; sales promotion and hedonic influence simultaneously on impulsive buying on Shopee e-commerce consumers.